Comparison of “framework Shuffling” and “CDR Grafting” in humanization of a PD-1 murine antibody - Wang, Yongmei; Chen, Yi-Li; Xu, Hui; Rana, Gul E.; Tan, Xiaorong; He, Mengying; Jing, Qingqing; Wang, Qi; Wang, Guifeng; Xie, Zuoquan; Wang, Chunhe (Frontiers in Immunology, 2024)
Introduction Humanization is typically adopted to reduce the immunogenicity of murine antibodies generated by hybridoma technology when used in humans. Methods Two different strategies of antibody humanization are popularly employed, including “complementarity determining region (CDR) grafting” and “framework (FR) shuffling” to humanize a murine antibody against human programmed death-1 (PD-1), XM PD1. In CDR-grafting humanization, the CDRs of XM PD-1, were grafted into the human FR regions with high homology to the murine FR counterparts, and back mutations of key residues were performed to retain the antigen-binding affinities. While in FR-shuffling humanization, a combinatorial library of the six murine CDRs in-frame of XM PD-1 was constructed to a pool of human germline FRs for high-throughput screening for the most favorable variants. We evaluated many aspects which were important during antibody development of the molecules obtained by the two methods, including antibody purity, thermal stability, binding efficacy, predicted humanness, and immunogenicity, along with T cell epitope prediction for the humanized antibodies. Results While the ideal molecule was not achieved through CDR grafting in this particular instance, FR-shuffling proved successful in identifying a suitable candidate. The study highlights FR-shuffling as an effective complementary approach that potentially increases the success rate of antibody humanization. It is particularly noted for its accessibility to those with a biological rather than a computational background. Discussion The insights from this comparison are intended to assist other researchers in selecting appropriate humanization strategies for drug development, contributing to broader application and understanding in the field.